Foxl2 is required for commitment to ovary differentiation - Ottolenghi, Chris; Omari, Shakib; Garcia-Ortiz, J Elias; Uda, Manuela; Crisponi, Laura; Forabosco, Antonino; Pilia, Giuseppe; Schlessinger, David (Human molecular genetics, 2005)
Genetic control of female sex differentiation from a bipotential gonad in mammals is poorly understood. We find that mouse XX gonads lacking the forkhead transcription factor Foxl2 form meiotic prophase oocytes, but then activate the genetic program for somatic testis determination. Pivotal Foxl2 action thus represses the male gene pathway at several stages of female gonadal differentiation. This suggests the possible continued involvement of sex-determining genes in maintaining ovarian function throughout female reproductive life.